Sīkdisperso grunšu klasificēšana pēc to plasticitātes - Meijere, Jolanta (Latvijas Universitāte, 2011)
Meijere, J. 2011. Sīkdisperso grunšu klasificēšana pēc to plasticitātes. Bakalaura darbs. Latvijas Universitāte, Rīga. 37 lpp. Bakalaura darba mērķis ir sīkdisperso grunšu identifikācijas parametru novērtējums. Bakalaura darbā pētītas sīkdisperso grunšu fizikālās īpašības un to savstarpējās sakarības. Salīdzinot plūstamības robežu vērtības, kas iegūtas izmantojot krītošā un Vasiļeva konusus konstatēts, ka starp iegūtajām vērtībām pastāv lineāra atkarība R2=0,94. Darbā aprakstītas Latvijā biežāk pielietotās grunšu klasifikācijas sistēmas un veikta pētīto grunšu klasificēšana. Secināts, ka atšķirīgās pieejas, iedalot gruntis sīkdispersās un rupjdrupu, tādējādi radot grūtības pētījumu rezultātu salīdzināšanā. Atslēgvārdi: inženierģeoloģija, krītošais konuss, Vasiļeva konuss, Aterberga robežas, klasifikācijas sistēmas.

Meijere, J. 2011. Classification of fine-grained soils according to their plasticity. Bachelors paper. University of Latvia, Riga. 37 pp. Main task of the Bachelor paper is estimate of fine-grained soils index parameters criteria. In Bachelor paper are analyzed physical characteristics of fine-grained soils and their interrelationships. It has been compared determination of liquid limits with two different methods – fall cone and Vasilev cone and the data analysis proves that the result give very satisfy correlation which is shown by the coefficient of determination, R2 = 0.94. In Bachelor paper has been describe some of the most common use classification systems in Latvia. The paper concludes that different approaches for dividing soils in to the coarse-grained and fine-grained groups, makes it difficult to compare breakdowns for different soil types. Keywords: engineering geology, fall cone, Vasilev cone, Atterberg limits, classification systems.
Classification of fine-grained soils according to their plasticity
Keywords: Ģeoloģija